An experimental procedure based on infrared thermography for the assessment of crack density in quasi-isotropic CFRP. (December 2021) - De Finis, Rosa; Palumbo, Davide; Galietti, Umberto
Highlights: A novel procedure for detecting 90°ply cracks based on thermal signal analysis. A novel parameter for assessing the crack density without stopping the test. The measured crack density matches well the one predicted by analytical models. The crack density allows the determination of the characteristic damage state. Abstract: The crack density is a very well-known damage parameter representing the actual mechanical state of the material in terms of stiffness degradation. In effect, for laminates presenting off-axis laminae, crack density is useful for determining the "characteristic damage state" (CDS) that is related the load carrying capability of the laminate. In literature, analytical and empirical models in addition with experimental procedures are used for the assessment of crack density. However, in all cases, accurate experimental setups and time-consuming analyses are required. In this work, a novel procedure is proposed for performing contactless measurements of crack density during constant amplitude fatigue tests by using temperature second amplitude harmonic without any material properties assessment. The results of the experimental campaign in terms of crack density assessed at different stress level are in good agreement with those provided by analytical models and demonstrate the capability of the proposed parameter provided by the thermal signal analysis to describe damage mechanisms affecting the specific material. The proposed procedure leads to estimate the crack density in those applications where it is difficult to detect transverse crack with a direct measurement using common experimental techniques.